Enhancing the Students’ Achievement of Simple Future Tense by Using Song - Hartiwi, Juni (LinguaScopes: International Journal of Language Education, 2025)
This study aims to determine whether songs can assist students in improving their achievement y in the Simple Future Tense. The subject of the research is second semester EFL students at Bandar Lampung University. The research results reveal that students' skills in the Simple Future Tense significantly improve after the intervention. This suggests that songs may serve as an efficient resource for mastering Simple Future Tense.